Neonatal GLP1R activation limits adult adiposity by durably altering hypothalamic architecture - Andrea V. Rozo; Daniella A. Babu; PoMan A. Suen; David N. Groff; Randy J. Seeley; Rebecca A. Simmons; Patrick Seale; Rexford S. Ahima; Doris A. Stoffers (Elsevier, 2017)
Objective: Adult obesity risk is influenced by alterations to fetal and neonatal environments. Modifying neonatal gut or neurohormone signaling pathways can have negative metabolic consequences in adulthood. Here we characterize the effect of neonatal activation of glucagon like peptide-1 (GLP-1) receptor (GLP1R) signaling on adult adiposity and metabolism. Methods: Wild type C57BL/6 mice were injected with 1 nmol/kg Exendin-4 (Ex-4), a GLP1R agonist, for 6 consecutive days after birth. Growth, body composition, serum analysis, energy expenditure, food intake, and brain and fat pad histology and gene expression were assessed at multiple time points through 42 weeks. Similar analyses were conducted in a Glp1r conditional allele crossed with a Sim1Cre deleter strain to produce Sim1Cre;Glp1rloxP/loxP mice and control littermates. Results: Neonatal administration of Ex-4 reduced adult body weight and fat mass, increased energy expenditure, and conferred protection from diet-induced obesity in female mice. This was associated with induction of brown adipose genes and increased noradrenergic fiber density in parametrial white adipose tissue (WAT). We further observed durable alterations in orexigenic and anorexigenic projections to the paraventricular hypothalamic nucleus (PVH). Genetic deletion of Glp1r in the PVH by Sim1-Cre abrogated the impact of neonatal Ex-4 on adult body weight, WAT browning, and hypothalamic architecture. Conclusion: These observations suggest that the acute activation of GLP1R in neonates durably alters hypothalamic architecture to limit adult weight gain and adiposity, identifying GLP1R as a therapeutic target for obesity prevention.